Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1037/a0038871
|View full text |Cite
|
Sign up to set email alerts
|

Masculinities, alcohol consumption, and sexual risk behavior among male tavern attendees: A qualitative study in North West Province, South Africa.

Abstract: Alcohol consumption is strongly associated with sexual risk behavior and HIV infection in sub-Saharan Africa. This article seeks to explore the role of constructions of masculinity in men’s drinking and sexual risk behavior in drinking venues (bars and taverns) in 2 rural villages of North West Province, South Africa. Ten focus groups were conducted with 58 bar patrons and servers. Four focus groups consisted of female bar patrons, 4 consisted of male bar patrons, and 2 consisted of male bar managers and serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
(92 reference statements)
0
17
0
Order By: Relevance
“…Indeed, complex relationships appear to exist between alcohol and sex. For example, while some individuals use alcohol to pay for sexual intercourse [ 15 17 ] or to do gender in sexual contexts [ 18 ], others use drunkenness as a ready-made excuse to engage in unplanned sexual activities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, complex relationships appear to exist between alcohol and sex. For example, while some individuals use alcohol to pay for sexual intercourse [ 15 17 ] or to do gender in sexual contexts [ 18 ], others use drunkenness as a ready-made excuse to engage in unplanned sexual activities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings chime with those from Zimbabwe (Skovdal et al, 2011) and Uganda (Mburu et al, 2014) where participants also noted how their male relative did not want to accept the patient-persona, deliberately ignoring instructions received by the health worker, and instead turned to harmful behaviours, such as drinking alcohol, as a way perhaps to ‘normalise’ or ‘end’ life. A number of studies in sub-Saharan Africa have highlighted how alcohol use is linked to men’s concern about demonstrating masculinity (Brown, Sorrell, & Raffaelli, 2005), and the implications of this for HIV-related behaviour (Nkosi, Rich, Kekwaletswe, & Morojele, 2016; Rich, Nkosi, & Morojele, 2015; Woolf-King & Maisto, 2011). This study supports the ample literature that highlights how masculine norms come to shape men’s engagement with HIV risk, prevention methods and treatment services.…”
Section: Discussionmentioning
confidence: 99%
“…The hazardous drinking that occurs in alcohol-serving venues may increase women’s vulnerability to sexual objectification, and female venue patrons may experience stigma because alcohol-serving venues are traditionally seen as “masculine establishments” (24,36,37). Women who choose to attend venues may be different from the broader population of women in South Africa with regard to their alcohol use, sexual risk behaviors, and their social support outside of the venues.…”
Section: Discussionmentioning
confidence: 99%
“…Venue-specific social support was not shown to reduce HIV-related sexual risk behaviors among men in this setting. Because venues are traditionally male-dominated spaces, support from other venue patrons may instead promote traditional gender norms around masculinity (36,37). Prior research conducted in South Africa has demonstrated that inequitable gender attitudes are associated with risky sexual behaviors as a mechanism for men to exert dominance and control over women (41,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation